1066 A proposed pilot to integrate health and social care to tackle child inequality: the Sparkbrook Children's Zone, Birmingham. (17th August 2022) - Dutton, Fran; Wolhuter, Caroline; Kaur, Simarjeet; Rao, Satish; Bird, Christopher
Abstract : Aims: A decade of austerity, exacerbated by Covid-19, saw 30% of UK children living below the official poverty line in 2021. The hollowing out of children's frontline services has also marked a rise in inappropriate attendances (IAs) to urgent care (1) and to specialist services. (2) NHS England and the Royal College of Paediatrics and Child Health advocate redirecting children's health and social care back to the community through integrated care services (ICS) and early help support.(3) There is early evidence that an integrated approach reduces secondary care usage and may deliver better outcomes for families.(4) We aim to pilot an integrated service comprising community groups, Early Help, GPs and paediatricians to deliver place-based health and social support to children in Sparkbrook, Birmingham, an area of high deprivation. Methods: Identify an area in Birmingham, UK, with both high levels of deprivation and inappropriate attendances (IAs) to the Emergency Department (ED) to begin piloting ICS and place-based care for CYP, using city council and hospital data. Carry out community engagement work to identify the health and social care issues most important to families when setting up the pilot. Results: The Sparkbrook ward was chosen based on data showing high levels of deprivation, a young population (35% of the ward is <18 years-old compared to 20% nationally), high rates of infant mortality (7.9/1, 000 compared to 3.9 nationally) (5) and high numbers of IAs to the ED, Birmingham Children's Hospital (mean number of IAs to ED was 41 per ward but for Sparkbrook, 289 IAs (May 2018-April 2019), (see figure 1 ). We held four community engagement sessions, which highlighted that any new service for children should be: local and accessible; have a friendly environment where people able to speak their language; a 'walk-in' type centre; opening hours after school and some weekends; provision of health advice, eg workshops; children's activities (more details figure 2 ). Conclusion: With funding from NHS England and Birmingham Children's Trust, a weekly clinic is in set-up in the Sparkbrook ward, which will open after school, where community groups, Early Help, GPs, dental services and paediatricians will work alongside each other to deliver place-based health and social care to a population of 14, 000 children, prioritising early intervention programmes, health promotion (immunisations, healthy weight) and common chronic conditions (asthma, eczema and constipation). References: McHale P, Wood S, Hughes K, Bellis MA, Demnitz U, Wyke S. Who uses emergency departments inappropriately and when - a national cross-sectional study using a monitoring data system. BMC Medicine. 2013 Dec 13;11(1):258. Williams M, Franklin J. Children and young people's services: Spending 2010-11 to 2019-20. 2021 Jul. Royal College Of Paediatrics and Child Health. Paediatrics 2040: Our vision for the future of paediatrics in the UK. London; 2021 Feb. Montgomery-Taylor S, Watson M, Klaber R. Child Health General Practice Hubs: a service evaluation. Archives of Disease in Childhood. 2016 Apr;101(4):333–7. Birmingham Public Health Intelligence Team. Birmingham Health Profiles: Hall Green Constituency 2019. Birmingham; 2018.